Kepemimpinan Kiai Pondok Pesantren Dalam Pengembangan Wisata Religi Menurut Perspektif Kepemimpinan Max Weber - Ratih Dwi Habibah; Aminah Dewi Rahmawati (Universitas Trunojoyo Madura, 2023)
This research is motivated by the researcher's interest in Bangkalan being the gateway to Madura Island which has tourism potential, ranging from natural tourism, culinary tourism, especially religious tourism. In Bangkalan there are many Islamic boarding schools and their people who have a high level of religiosity. The figure of the kiai for the people of Bangkalan is a leader as a role model and savior. Therefore, in the life of the people of Bangkalan, kiai have an important role. With that, kiai can become stakeholders in the development of religious tourism in Islamic boarding schools. The research objectives were first, to find out the meaning of the kiai for the role of Islamic boarding schools and second, the practice of kiai in managing Islamic boarding schools for the development of religious tourism using Max Weber's charismatic leadership theory. This study uses a qualitative method, a phenomenological approach which will further examine the events or experiences of the kiai. Researchers determine informants using purposive sampling method and using observation, interviews, and documentation to collect data. Researchers analyzed the data using three methods, namely data reduction, data presentation, and conclusions. The results of this study indicate that KH. Thoha interpreted that Islamic boarding schools could function as educational tours, while Kiai Rois interpreted that Islamic boarding schools could function as places of religious tourism and social tourism. This has been practiced directly by the two kiai through the management of the pondok by utilizing their charisma. Meanwhile, there is one kiai, namely KH. Makky who has a traditional leadership system that interprets Islamic boarding schools only as a place to study religion. And there is no KH action. Makky who manages Islamic boarding schools as the development of religious tourism.